STRATEGIES OF THE DIGITAL AGRICULTURAL SECTOR IN THE CONTEXT OF ENVIRONMENTAL AND ECONOMIC SECURITY - PІSHСHЕNKО, Oleg (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article analyzes the prerequisites and conditions of the digital agricultural sector strategy in the context of environmental and economic security. The aim of the study is to develop digitalization scenarios in the agri-food sector that are directly related to agricultural policy.It is established that the key consequence of the analysis of scenarios for policy development is the need for strategic development of digital infrastructure for Agricultural Policy. The prospects and consequences of digitalization in the agri-food sector and in agricultural policy are uncertain. In order to prepare stakeholders in agricultural policy to meet the uncertain future challenges associated with digitalization, four scenarios for the corresponding digitalization policy of the agri-food sector were developed. For all these scenarios, gaps have been identified in relation to important goals of European Agricultural Policy. They are used to obtain measures that address policy performance deficiencies in scenarios.Digitalization of the entire process, from sowing and harvesting to warehousing and distribution, strengthens the link between different stakeholders in the agroecosystem. Digitalization has also improved visibility in the supply chain for different participants, making the process more transparent and highly efficient.The development of agricultural policy should take into account the wide range of likely future digitalization of the agri-food sector proposed by our study. It is also necessary to assess technological development and ways of relevant digitalization. This could follow the perspective of responsible research and innovation on a more detailed scale, which could inform our agricultural policy scenarios and objectives.
Keywords: strategies; digital agricultural sector; conditions; environmental and economic security